Using multiple types of studies in systematic reviews of health care interventions--a systematic review. - Frank Peinemann; Doreen Allen Tushabe; Jos Kleijnen (PLoS ONE)
Background A systematic review may evaluate different aspects of a health care intervention. To accommodate the evaluation of various research questions, the inclusion of more than one study design may be necessary. One aim of this study is to find and describe articles on methodological issues concerning the incorporation of multiple types of study designs in systematic reviews on health care interventions. Another aim is to evaluate methods studies that have assessed whether reported effects differ by study types. Methods and findings We searched PubMed, the Cochrane Database of Systematic Reviews, and the Cochrane Methodology Register on 31 March 2012 and identified 42 articles that reported on the integration of single or multiple study designs in systematic reviews. We summarized the contents of the articles qualitatively and assessed theoretical and empirical evidence. We found that many examples of reviews incorporating multiple types of studies exist and that every study design can serve a specific purpose. The clinical questions of a systematic review determine the types of design that are necessary or sufficient to provide the best possible answers. In a second independent search, we identified 49 studies, 31 systematic reviews and 18 trials that compared the effect sizes between randomized and nonrandomized controlled trials, which were statistically different in 35%, and not different in 53%. Twelve percent of studies reported both, different and non-different effect sizes. Conclusions Different study designs addressing the same question yielded varying results, with differences in about half of all examples. The risk of presenting uncertain results without knowing for sure the direction and magnitude of the effect holds true for both nonrandomized and randomized controlled trials. The integration of multiple study designs in systematic reviews is required if patients should be informed on the many facets of patient relevant issues of health care interventions.